Saving the pandas - Waring, Rob (Australia : Heinle, Cengage Learning, 2009)
Describes how the people of China are trying to save the endangered giant pandas and includes questions, definitions, and a vocabulary list
'National geographic' - cover
Book is accompanied by one DVD, entitled'Saving the pandas' bearing the same call number and available at Bahagian Koleksi Media
Keywords: English language -- Textbooks for foreign speakers; Pandas